Without a brew - Alexander, Ellie (Alexander, Ellie. Sloan Krause mysteries., 2020)
"Amateur sleuth Sloan Krause delves into a murderous winter wonderland in another delightful mystery from cozy writer Ellie Alexander, Without a Brew. It's winter in the Bavarian village of Leavenworth, Washington, which for Sloan Krause means lots of layers, pine and citrus-flavored craft beers, and getting the new guest rooms at Nitro, the brewery where she works, into tip top shape before the next weekend's IceFest. Unfortunately, Sloan and her boss Garrett are learning that not every guest in the brewery is up for a hopping good time. While the couple staying with them, Brad and Ali, seem completely smitten, a quartet arrives in the evening demanding rooms and showing off flashy Seattle credentials. Sloan and Garrett are less than impressed, but agree to rent rooms to the quarrelsome quartet. The final guest, Liv, wasn't planning on an overnight stay in Leavenworth, but seems eager to take Sloan up on the offer of sanctuary from the snow-at least before she has a strange run in with local mechanic Taylor, to say nothing of the knowing looks and even physical altercations that take place between Liv and the other guests. Sloan could be imagining things, but when Liv's room is found trashed the next morning, a hateful message painted on her car, and Liv herself is no where to be found, Sloan is convinced another mystery is brewing. And with many of the potential suspects hunkering down under Nitro's roof, she knows her co-workers and friends won't be safe until serves up the killer a hoppy pint of justice"--